2015
DOI: 10.1371/journal.pone.0124689
|View full text |Cite
|
Sign up to set email alerts
|

Viral Dose and Immunosuppression Modulate the Progression of Acute BVDV-1 Infection in Calves: Evidence of Long Term Persistence after Intra-Nasal Infection

Abstract: Bovine viral diarrhoea virus (BVDV) infection of cattle causes a diverse range of clinical outcomes from being asymptomatic, or a transient mild disease, to producing severe cases of acute disease leading to death. Four groups of calves were challenged with a type 1 BVDV strain, originating from a severe outbreak of BVDV in England, to study the effect of viral dose and immunosuppression on the viral replication and transmission of BVDV. Three groups received increasing amounts of virus: Group A received 102.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 34 publications
(36 reference statements)
6
33
0
Order By: Relevance
“…Interestingly, all groups showed a second peak in viral RNA, which was particularly apparent in the Vaccine-NP and IAV group, where the two groups show the same trend albeit offset. Viral RNA was cleared from the blood of the Vaccine-NP and IAV groups on day 21 and 18, respectively, whereas, viral RNA was still detectable in the blood of Control-NP animals at the termination of the experiment (day 24 post-challenge), which is in line with another observation the more pathogenic strains such as Ho916 induce a persistent infection in post-natal infection 32 .
Figure 5 Detection of BVDV in the blood of vaccinated animals following challenge infection.
…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, all groups showed a second peak in viral RNA, which was particularly apparent in the Vaccine-NP and IAV group, where the two groups show the same trend albeit offset. Viral RNA was cleared from the blood of the Vaccine-NP and IAV groups on day 21 and 18, respectively, whereas, viral RNA was still detectable in the blood of Control-NP animals at the termination of the experiment (day 24 post-challenge), which is in line with another observation the more pathogenic strains such as Ho916 induce a persistent infection in post-natal infection 32 .
Figure 5 Detection of BVDV in the blood of vaccinated animals following challenge infection.
…”
Section: Resultssupporting
confidence: 85%
“…On 41 dpv, all cattle received an intranasal inoculation with 5 × 10 6 TCID 50 BVDV-1a Ho916 in 2 ml BT medium, which was confirmed by back titration. Clinical scores and rectal temperatures were monitored prior to viral challenge and on a daily basis subsequently 32 . Blood samples were collected longitudinally over the course of vaccination and challenge to assess serum antibody and peripheral blood T cell IFN-γ responses, and to monitor for viral loads.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the short duration for viral excretion in TI animals, it has been reported that it may be sufficient at sustaining infection within a herd in the absence of a PI animal (Collins, Heaney, Thomas, & Brownlie, 2009;Moen et al, 2005) although other experimental studies do not support this (Nickell, White, Larson, Renter, & Sanderson, 2011;Niskanen, Lindberg, & Traven, 2002;Sarrazin et al, 2014). Outbreaks of BVD pestiviruses have also occurred due to the persistence of the virus in the reproductive organs, ovaries and testes, of TI animals (Collins et al, 2009;Niskanen, Alenius, et al, 2002;Strong et al, 2015). While the risk of transmission by TI animals is considered much lower than the risk posed by PI animals, the full extent of viral shedding and persistence of virus in TIs and their ability to maintain infection within a population needs further investigation.…”
Section: Vertical Transmission Of Bvd Occurs When Bovine Pestivirusesmentioning
confidence: 99%
“…1–5 The extent of disease appears to be dependent on the level of immunity of the animal and pathogenicity of the virus strain. 6 7 …”
Section: Introductionmentioning
confidence: 99%